The decision making process of being palliative volunteer - Ni Putu Wulan Purnama Sari; Nia Novita Sari (International Journal of Public Health Science (IJPHS), 2019)
Palliative care delivery in Surabaya community, Indonesia, is in collaboration with palliative volunteers. The decision to be palliative volunteer was not easy, mainly because of financial matter, time limitation, and role conflict. This study aimed to analyze the decision making process of being a palliative volunteer in Surabaya. This qualitative study involved 13 female palliative volunteers under the supervision of Public Health Center (PHC) of Rangkah. In-depth-interview was used for data collection. Instruments used were interview guideline, observation sheet, and voice recorder. Collaizi method was used for data analysis. The majority was 40-50 years old, married, housewife, and high school graduated. Each participant manages 5-8 patients to be home-visited regularly. The driving force and the reason to persistently be a palliative volunteer was the willingness to help others in need. The major entry point acting as stimulus was health care professional in the Rangkah PHC. The decision making model applied was descriptive model, because despite of insufficient information through various entry points but the decision made was fast and persistent.